COLLOQUIAL LANGUAGE USED IN MOVIE SCRIPT ADA APA DENGAN CINTA 1 - Imam Arif Hidayat; Muhammad Kiki Wardana (JOURNAL OF LANGUAGE, 2021)
This study is conducted to examine colloquial expression in the movie script Ada Apa dengan Cinta I. Colloquial Language is the linguistic style used for casual communication. The method applied in this study is qualitative approach. The data shows that there are 28 occurances of colloquial expression in the movie script. The expressions involve five types. They are slang, jargon, provanity, contraction and idiom. The most dominat expression used in the movie is slang with 42.9% occurances. The second position is provanity with 25% occurances. Then, the next level is jargon with 17.9%, contraction with 10.7%, and the last is idiom with only 3.5% occurances. The result shows that the movie script presents a casual conversation. Most situation of the conversation is informal. Moreover, this movie script is identical with teenagers as the most characters are teenagers. The teenagers tend to use such casual conversations. Besides, the result proves that this movie script also presents a local dialect of Bahasa Indonesia. It is Jakarta dialect since the setting is in that region. Therefore, it is concluded that this movie is characterized with Jakarta dialect and teenager’s casual conversation.